Is Facet Tropism Associated with Increased Risk of Disc Herniation in the Lumbar Spine? - Ghandhari, Hassan (Asian Spine J, 2018)
STUDY DESIGN: Retrospective case control study. PURPOSE: In current study, we compared the incidence of facet tropism (FT) in patients with lumbar disc herniation and normal controls. OVERVIEW OF LITERATURE: It has been suggested that FT can be associated with increased risk of lumbar disc herniation. METHODS: A total of 66 and 63 patients with L4/L5 and L5/S1 disc herniation, respectively, were evaluated in the present study. The control group comprised 61 normal subjects. Facet joint angle was measured using axial magnetic resonance images. The FT was defined as a difference of >10° between the right and left facet joints. The incidence of FT was compared between patients and controls. We also investigated the relationship between facet orientation (sagittal or coronal) and side of disc herniation. RESULTS: The incidence of FT at the L4/L5 level was significantly higher in patients with disc herniation (48.5% vs. 26.2%, p =0.01), while it was found to be the same at the L5/S1 level in patients and controls (50.8% vs. 36%, p =0.098). Among the 64 patients with FT, intervertebral disc herniation occurred significantly toward the more sagittally oriented facet joint in 41 patients (p <0.05). CONCLUSIONS: FT is associated with increased risk of L4/L5 intervertebral disc herniation, but not at the L5/S1 level. In addition, disc herniation occurred toward the more sagittally oriented facet joint.